Are U.S. Schools Discriminating When Suspending Students With Disabilities? A Best-Evidence Synthesis. (October 2019) - Morgan, Paul L.; Wang, Yangyang; Woods, Adrienne D.; Mandel, Zoe; Farkas, George; Hillemeier, Marianne M.
We examined whether U.S. schools systemically discriminate when suspending or otherwise disciplining students with disabilities (SWD). Eighteen studies met inclusion criteria. We coded 147 available risk estimates from these 18 studies. Of four studies including individual-level controls for infraction reasons, over half of the available estimates (i.e., 14 of 24, or 58%) failed to indicate that SWD were more likely to be suspended than otherwise similar students without disabilities. Of the seven available estimates adjusted for the strong confound of individual-level behavior, most (i.e., five of seven, or 71%) failed to indicate that SWD were more likely to be suspended. The other two estimates indicating SWD were more likely to be suspended were from one study. We also examined whether SWD were less likely to be suspended than otherwise similar students without disabilities. There was no strong evidence of this. Empirical evidence regarding whether U.S. schools discriminate when disciplining SWD is currently inconclusive.